Pemanfaatan Limbah Cangkang Kerang sebagai Strategi Pemberdayaan UMKM: Utilization of Shellfish Shell Waste as a Strategy for MSME Empowerment - Anisyah Achmad; Adeltrudis Adelsa Danimayostu; Rahmi Nurdiana; Kanthi Permaningtyas Tritisari; Martina Dini Dwi Rahmawati; Intaha Irsani; Melfin Fakhrul Asyiqin; Yunita Mudmaynah; Vebbina Ginting; Hanafi Saiful Anwar (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Training on the utilization of shellfish shell waste is one strategy to support environmental management while increasing the economic value of micro, small, and medium enterprises (MSMEs). This study aimed to evaluate the development of participants’ knowledge and perceptions through a pre-test and post-test approach conducted in two stages of training. A descriptive quantitative method was employed, with 58 participants in the first training session and 38 in the second. The pre-test administered during the first session measured participants’ general knowledge of shellfish shell waste utilization, while the post-test conducted during the second session assessed participants’ advanced understanding, particularly regarding food safety and SPP-IRT licensing. The results showed that participants had a relatively high level of initial knowledge and were able to follow the advanced technical material in the subsequent stage. In addition, participants’ perceptions of the training indicated very high levels of participation and expectations. These findings suggest that a staged training approach can enhance MSMEs’ readiness to implement the utilization of shellfish shell waste in a more practical and sustainable manner.